A Qualitative Investigation of the Dynamics and Complexity of Language Learner Beliefs through Written Protocols - Ritzau, Ursula (Linguistik Online, 2014)
During recent years, language learner beliefs have increasingly been studied through qualitative, learner-centred methods, and the development and dynamics of language learner beliefs have been brought into focus. This paper analyses the development and complexity of beliefs expressed by three university students of Danish as a foreign language in Switzerland. A qualitative method inspired by Grounded Theory is employed and proves to be fruitful for pinpointing the dynamics and complexities of the beliefs. Data are collected through written protocols in German and Danish. The data collection phase stretches over nearly a year and a half, which facilitates a detailed exploration of temporal changes in the beliefs expressed by the study participants.